De novo CLTC variants are associated with a variable phenotype from mild to severe intellectual disability, microcephaly, hypoplasia of the corpus callosum, and epilepsy - Nabais Sá, Maria J.; Venselaar, Hanka; Wiel, Laurens; Trimouille, Aurélien; Lasseaux, Eulalie; Naudion, Sophie; Lacombe, Didier; Piton, Amélie; Vincent-Delorme, Catherine; Zweier, Christiane; Reis, André; Trollmann, Regina; et al. (Genetics in Medicine, 2019)
Purpose: To delineate the genotype–phenotype correlation in individuals with likely pathogenic variants in the CLTC gene. Methods: We describe 13 individuals with de novo CLTC variants. Causality of variants was determined by using the tolerance landscape of CLTC and computer-assisted molecular modeling where applicable. Phenotypic abnormalities observed in the individuals identified with missense and in-frame variants were compared with those with nonsense or frameshift variants in CLTC. Results: All de novo variants were judged to be causal. Combining our data with that of 14 previously reported affected individuals (n = 27), all had intellectual disability (ID), ranging from mild to moderate/severe, with or without additional neurologic, behavioral, craniofacial, ophthalmologic, and gastrointestinal features. Microcephaly, hypoplasia of the corpus callosum, and epilepsy were more frequently observed in individuals with missense and in-frame variants than in those with nonsense and frameshift variants. However, this difference was not significant. Conclusions: The wide phenotypic variability associated with likely pathogenic CLTC variants seems to be associated with allelic heterogeneity. The detailed clinical characterization of a larger cohort of individuals with pathogenic CLTC variants is warranted to support the hypothesis that missense and in-frame variants exert a dominant-negative effect, whereas the nonsense and frameshift variants would result in haploinsufficiency.
CRIS-Team Scopus Importer:2019-12-10
Keywords: CLTC; intellectual disability; neurodevelopmental disorder